Phosphodiesterase 7 inhibitor reduces stress-induced behavioral and cytoarchitectural changes in C57BL/6J mice by activating the BDNF/TrkB pathway - Dong, Jiahao; Wei, Ran; Zong, Fangjiao; Wang, Zhe; Ma, Shengyao; Zhao, Wei; Lin, Yuanyuan; Zhang, Aixin; Lan, Ge; Zhang, Fang; Zhang, Han-Ting (Frontiers in Pharmacology, 2024)
Background: Phosphodiesterase 7 (PDE7) plays a role in neurological function. Increased expression and activity of PDE7 has been detected in several central nervous system diseases.However, the role of PDE7 in regulating stress levels remains unclear. Thus, this study aimed to determine whether and how PDE7 involved in the stress-induced behavioral and neuron morphological changes.The single prolonged stress (SPS) was used to build a stress exposure model in C57BL/6J mice and detected PDE7 activity in hippocampus, amygdala, prefrontal cortex and striatum. Next, three doses (0.2, 1, and 5 mg/kg) of the PDE7 inhibitor BRL-50481 were intraperitoneally administered for 10 days, then behavioral, biochemical, and morphological tests were conducted.Results: PDE7 activity in hippocampus of mice significantly increased at all times after SPS. BRL-50481 significantly attenuated SPS induced anxiety-like behavior and fear response in both context and cue. In addition, BRL-50481 increased the levels of key molecules in the cAMP signaling pathway which were impaired by SPS. Immunofluorescent staining and Sholl analysis demonstrated that BRL-50481 also restored the nucleus/cytoplasm ratio of hippocampal neurons and improved neuronal plasticity. These effects of BRL-50481 were partially blocked by the TrkB inhibitor ANA-12.Conclusions: PDE7 inhibitors attenuate stress-induced behavioral changes by protecting the neuron cytoarchitecture and the neuronal plasticity in hippocampus, which is mediated at least partly through the activation of BDNF/TrkB signaling pathway. These results proved that PDE7 is a potential target for treating stress-induced behavioral and physiological abnormalities.